The Effect of System Quality, Information Quality, and Service Quality on the Net Benefits of Hospital Management Information Systems, With System Use and User Satisfaction as Mediating Variables at Hospital X, Tangerang City - Irzanto Yunda; Sandra Dewi; MF. Arrozi Adhikara (Interdisciplinary Social Studies, 2026)
This paper is to evaluate the use of the Hospital Information System (SIMRS) at Hospital X which has been used so far. The aim of this research is to examine the influence of system quality, information quality, service quality, usage and user satisfaction on net benefits. Researchers use the DeLone and McLean method because this model is known as a simple model but is considered quite valid by researchers in measuring an information system. This research was conducted on the population of Hospital X staff who used SIMRS using a questionnaire. The research results show that system quality has no effect on usage. Then system quality affects user satisfaction. The results of this research also show that information quality and service quality jointly influence user usage and satisfaction. Additionally, usage and user satisfaction influence net benefits. As a mediator of use and user satisfaction, it also influences system quality, information quality and service quality on net benefits. It is hoped that the results of this research can be a reference for developing the potential of SIMRS to be even better and provide information regarding the factors that influence the quality of SIMRS at Hospital X.